Maturogenesis Part 2. Irrigation Protocols, Intracanal Medication - R. Žižka; J. Šedý; J. Škrdlant; T. Anděl; N. Němcová (Česká Stomatologie a Praktické Zubní Lékařství, 2016)
Objectives: Disinfection of the root canal system is one of the most important steps in revascularization treatment. If the disinfection of root canal system is inadequate, the succes rate is decreased. On the other hand if the disinfection of root canal system is too aggresive, the probability of new hard tissue on the root canal walls is less probable. In this second article, bacterial contamination of root canal system and its decontamination are considered. Particular irrigation solutions are analysed from both their antimicrobial activity as well as translational medicine. Furthermore, possible intracanal medications, including suggestion of the new triple antibiotic paste are explored.